2018
DOI: 10.1021/acs.langmuir.8b02383
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Complex Formation between Polysaccharides and Protein Microgels To Influence Particle Stabilization of W/W Emulsions

Abstract: Protein particles were complexed with polysaccharides, and the effect on their capacity to stabilize water-in-water (W/W) emulsions was investigated. Protein microgels were formed by heating aqueous solutions of whey protein isolate. The microgels were subsequently mixed with anionic or cationic polysaccharides: κ-carrageenan (κ-car) or chitosan, respectively. The molar mass and radius of the complexes formed in dilute microgel suspensions (40 mg/L) were characterized by light scattering techniques as a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Whereas the MG clearly adsorbed at the interface (Figure 5B), no accumulation of FITC-PEC at the interface can be seen (Figure 5A), showing that no complexation had occurred between PEC and MG. It was shown elsewhere, using the same methodology, that κ-carrageenan (KC) forms complexes with MG only below pH 5.5 [14]. We found that complexes between MG and PEC also started to be formed only below pH 5.5.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Whereas the MG clearly adsorbed at the interface (Figure 5B), no accumulation of FITC-PEC at the interface can be seen (Figure 5A), showing that no complexation had occurred between PEC and MG. It was shown elsewhere, using the same methodology, that κ-carrageenan (KC) forms complexes with MG only below pH 5.5 [14]. We found that complexes between MG and PEC also started to be formed only below pH 5.5.…”
Section: Resultssupporting
confidence: 61%
“…Attractive interaction between MG can be induced by reducing the pH, but this also leads to large-scale aggregation of MG within the bulk phases [23]. Large-scale aggregation can be avoided by the addition of anionic polysaccharides that bind to the MG at pH < 5.5 [14]. Elsewhere we will show that stable AMP-PUL emulsions can be obtained in this manner at low AMP and PUL concentrations by reducing the pH in the presence of well-chosen small amounts of anionic polysaccharide.…”
Section: Generalization To Other Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water-in-water (W/W) emulsions are slightly more exotic, arising mainly where biopolymer solutions phase separate into discrete microscopic regions far richer in one component than the other (Esquena, 2016), (Nicolai and Murray, 2017) (Dickinson, 2019) and all sorts of particles that would prefer not to be in at least one of the aqueous phases can end up concentrated at the W/W interface, preventing further growth of the phase regions via fusion or migration of components between them (Nguyen et al, 2015, Gonzalez-Jordan et al, 2016, Khemissi et al, 2018, Murray and Phisarnchananan, 2016.…”
Section: Examples Of Microgels As Interfacial Stabilizers In Food Sysmentioning
confidence: 99%
“…Like proteins, protein aggregates can complex with polysaccharides. However, few studies have shown the complexation of protein aggregates with polysaccharide and the effects on functional properties (Jones et al, 2011;Khemissi et al, 2018;Wang et al, 2019). The structure of protein aggregates should significantly affect electrostatic complexation of protein-polysaccharide and the functional properties of the complex, which is important in the development of new food ingredients.…”
Section: Introductionmentioning
confidence: 99%